Diagnosis of cervical cancer using effective hybrid model in Bangladesh - Saad-Ul-Kabir, Syed; Neeha, Ashwaq Noor; Ibnat, Rifah Nanjiba; Prottasha, Tanjila Haque; Ananna, Sadika Rahman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.